#### Answer

$y' = 2xcotx - x^{2}cosec^{2}x + \frac{2}{x^{3}}$

#### Work Step by Step

$y = x^{2}cotx - \frac{1}{x^{2}}$
$y' = 2xcotx - x^{2}cosec^{2}x + \frac{2}{x^{3}}$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$y' = 2xcotx - x^{2}cosec^{2}x + \frac{2}{x^{3}}$

$y = x^{2}cotx - \frac{1}{x^{2}}$
$y' = 2xcotx - x^{2}cosec^{2}x + \frac{2}{x^{3}}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.